‘Like the fish not in water’: How language and race mediate the social and economic inclusion of women migrants to Australia - Butorac, Donna (Monash University ePress, 2014)
Learning English is an important aspect of post-migration settlement in Australia, and new migrants with beginner to intermediate proficiency are strongly encouraged to attend government-subsidised English language classes. Underpinning the framing and delivery of these classes is a commitment to the discursive construction of Australia as an English-monolingual nation state, in which increased English proficiency will lead to new migrants gaining employment, thereby achieving an important benchmark of successful inclusion in Australian society. The assumption that English language acquisition leads to social and economic inclusion is not challenged within the settlement English program, and the language learner is seen as linguistically deficient in English, rather than as an emerging bi- or multilingual. Moreover, the ways that race, as well as gender, mediate both language learning and social inclusion are never problematised. This paper is based on data from a longitudinal ethnography that examines subjectivity in three interactional domains – family, society and work – in order to explore how language, race and gender impact on the post-migration settlement trajectories and sense of social inclusion of women migrants to Australia.